Tweet Fragmentation Technique: An Automatic Detection of Malicious Tweet on Social Networking - Ms. Sayema Kausar, Ms. Pranoti Mane, Mr. Shrikant Sonekar, (Design Engineering, 2021)
Immense volume of short messages that is tweets are being shared among various clients and information on long range informal communication locales and microblogging destinations, for example, Twitter, Facebook and so forth. Twitter gets more than 400 million tweets for every day. Constant examination is extremely troublesome and testing undertaking on such gigantic information likewise questioning and recovery of information is additionally troublesome. Such a huge number of tweets contain colossal measure of commotion and repetition. Existing frameworks were generally chipped away at the static and the constrained information. The different existing frameworks were proposed to address these issues and furthermore they gave some arrangement. Summarization is the way toward involving a content document in such way that short summary produced by using the essential keywords of the first document. There is need of dynamic way to deal with condense information delivered by Twitter feeds. This paper proposes the novel method, which produce the significant substance based summery inside less measure of time. We also propose to detect the malicious tweets for offline and online tweets. Especially, in the proposed framework multi-subject summarization is performed on the online dataset which thusly require the less measure of time when contrasted with the other existing framework. So time productivity is improved by using the proposed framework.